Maintenance Decision Support Fuzzy System in Small and Medium Industries Using Decision Making Grid - Tahir, Zulkifli; M.A., Burhanuddin; Anton, S P; Haron, H. (Advanced Computer Theory and Engineering, 2008)
This paper describes maintenance decision support fuzzy system for computerized maintenance management system (CMMS) data analysis in small and medium industries (SMIs). The problems are based on two factors that influence effect of machines maintenance, the downtime and the frequency of machine failures. The objective is to implement both factors into decision making grid (DMG) and then embedded it into maintenance decision support fuzzy system. Next, SMIs can implement this system to support their maintenance decision process